The Public View on Social Media Platforms: A Case Study of Pakistan - Toor , Shazia Ismail; Zaidi , Shamail Zehra; Waheed , Javaria; Siddiqui , Ayesha (Pakistan Journal of Humanities and Social Sciences, 2024)
Social media and the internet technologies are affecting society. The social media environment in which we live has a significant influence on our perceptions and beliefs. Specifically, social media plays a significant role in how information is accessed and how social and cultural environments are organized in the modern world. Social media has never failed to impress publics. From education and information to entertainment and leisure, social media has never disappointed its users. Similarly, it has transformed the way content is produced, distributed and consumed. Journalism has now become citizen journalism and reliance on traditional means of news have declined. This extensive incorporation of social media into society has encouraged number of perceptions. These views are often divided into positive and negative or mixed public opinions about social media. Traditional society like Pakistan is more critical of social media and its integration into other means of communication. Therefore, this study examines; the public view on social media platforms; a case study of Pakistan. It uses survey method and online questionnaire is sent to 50 university students, 50 housewives, 50 working males and 50 media practitioners. Demographics and other factor impact the view of social media among public.